Epidemiology of Neural Tube Defects and Their Distributions within a Cohort Study in Al-Diwaniyah Governorate - Hakim, Wissam Saleh (Medical Science Journal for Advance Research, 2025)
Background: Neural tube defect (NTD) may result from incomplete or complete failure of a neural tube to close during embryonic development. In areas where folic acid is not supplemented into the diet, the incidence of NTDs remains between 0.5 to 2 in every 1000 births. Objective is to assess the incidence of NTDs and plan comprehensive care pathways for children with open NTDs in Al Diwaniyah Iraq. Method: This diagnostic study spans of 22 years, with an encompassing all deliveries recorded at the maternity and child teaching hospital at Al Diwaniyah region in Iraq. Results: Of the 207 NTD patients evaluated, a birth prevalence rate of 9.4 per 1000 births was noted and a male to female ratio of approximately 3:1. The reports included spina bifida cases (66.6%), encephalocele cases (24.6%) and anencephalic cases (8.6%). 73.9 % or 153 of respondents who did not take folic acid during the first trimester. 134 (64.7%) mothers were discovered to belong to low income households, 20 (9.6%) very high income and 53 (25.6%) middle class. Of the 49 mothers in this study, only 38% were from urban regions while 62% were rural. 87% of the 163 cases had antenatal diagnosis conducted. Conclution: Folic acid supplementation is suitable for preventing the recurrence of neural tube defects (NTDs) in infants of high-risk women.